Moderate Way Implementing Rukyah and Hisab to Determine A New Moon in Ramadan - Abdullah A Afifi; Afifi Fauzi Abbas (IDRIS Darulfunun Institute, 2022)
Rukyah and hisab have already become critical discussions in Islamic knowledge. Controversy arose, and the debate continues today. Some scholars prefer to use one method over another, while some scholars today try to offer moderate approaches for better solutions and understanding. Scholars claim both rukyah and hisab using the prophet Muhammad's hadith references. In comparison, a modest society is accessible to apply rukyah as their way to determine the new Ramadhan, and some complex cultures are multicultural, multi sects, or have a wide coverage area. This complexity will affect the observation process's difficulty, accuracy, and potential differences. This situation needs sensible solutions to determine the new Ramadhan. This paper tries to elaborate on each approach used by scholars and authorities, its preconditions, and how the approaches should be moderated to determine the new moon optimally by developing a strategy that gives mutual feedback to each method.